Como fatores bióticos e abióticos podem influenciar a capacidade de resistência dos habitats às invasões e o potencial invasor de espécies não-nativas de macrófitas aquáticas submersas - Silveira, Márcio José da (2014)
Introductions of exotic species have become a prominent problem that ecologists and environmental managers have confronted in the last years, and the introductions have increased dramatically in recent decades. In addition, an emerging concern is that with climate change these introductions can exacerbate, causing several impacts on biodiversity. Therefore, understanding the mechanisms which lead non-native species to invade the different ecosystems is extremely important in order to minimize the causes and potential impacts of invasions. Aquatic plants have spread rapidly and invaded several environments, where they have caused severe impacts on biodiversity and ecological functions. Therefore, a great challenge for research on invasive plants is to develop the ability to predict the invasive potential of the species and the resistance of the habitats to invasions. Some hypotheses based on ecological theories can explain the success or failure in the introductions of non-native species in different habitats. Some researchers have directed their studies to answer as plantherbivore relationships can influence the establishment and spread of non-native plants. There are several studies indicating that herbivores may play an important role in the process invasion species. Environmental conditions and the availability of resources impose limitations to the different organisms that require of the individual's ecological strategies conditioned by historical and evolutionary restrictions. Therefore, restrictive conditions such as abiotic and biotic factors (e.g. sediment characteristics, temperature, competition with native species, etc.) operate as environmental filters that can reduce the chances of invasion and establishment of non-native species in various regions. However, the plastic responses demonstrated by some species can be a main means of adaptation to environmental heterogeneity, and this factor may increase the invasion potential of non-native species. Although several hypotheses are suggested and tested for biological invasions, the results about of the different mechanisms related to the invasive potential and quality of habitats are still contradictory and are far from being elucidated. However, different mechanisms might act jointly and sometimes synergistically on invasions. In this thesis, we carried out experimental and field observations to test these hypotheses separately and together to better understand the processes that lead to the invasion of non-native species in a new ecosystem.